An investigation of iot importance and viability of health records retrieval using electronic tags in pilgrimage - Latif A.I.; Othman M.; Ali N.B.; Suliman A.; Mahdi O.A. (Universiti Teknikal Malaysia Melaka, 2023)
Healthcare services is one of most important domains in the world. One of most crucial aspects of healthcare services is the need to make accurate healthcare decisions at the right time. Retrieving useful historical health records of patients in real-time is necessary to provide accurate healthcare decisions. Traditional health record systems such as paper-based system require time and effort to collect, manage, and retrieve patients' records. Electronic health record systems were adopted to allow healthcare staff to retrieve useful health records in real-time and consequently improve and speed up healthcare services. Although EHR is effective to serve patients in their local countries, the implementation of EHR for global purposes is still an issue and EHR is not always applicable for people who travel to other countries. One of the most important purposes for Muslims to travel is the pilgrimage journey to the Kingdom of Saudi Arabia (KSA) to perform religious rites. The millions of pilgrims converging there may need healthcare services and these services should be accomplished accurately in real-time which require electronic-based historical health records approaches. This study aims to investigate the importance and viability of IoT implementations to support retrieval of pilgrims' EHR using electronic tags. A questionnaire with 60 academic staff and interview with five experts from KSA were conducted to address the main aim of this study. The significance of the results shows that EHR supporting tag reading is a promising solution to enhance healthcare services and counter the challenges of EHR implementations in pilgrimage.